2008
DOI: 10.1539/joh.l8015
|View full text |Cite
|
Sign up to set email alerts
|

The Value of High Resolution Computed Tomography in the Diagnostics of Small Opacities and Complications of Silicosis in Mine Machinery Manufacturing Workers, Compared to Radiography

Abstract: The Value of High Resolution Computed Tomography in the Diagnostics of Small Opacities and Complications of Silicosis in Mine Machinery M a n u f a c t u r i n g W o r k e r s , C o m p a r e d t o Radiography: Jinkai SUN, et al. Division of Pneumoconiosis, School of Public Health, ChinaMedical University, China-The purpose of this study was to assess the value and usefulness of high resolution computed tomography (HRCT) in the diagnostics of small opacities and complications of silicosis in mine machinery man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Nevertheless, regardless of the nature of the dust exposure, HRCT is known to be more specific and sensitive than CXR in identifying pneumoconiosis . Furthermore, HRCT is more sensitive than radiography in revealing small nodules in the subpleural area and fissures, emphysema, early fibrotic changes, subpleural lines and parenchymal bands in coal workers' pneumoconiosis and asbestosis .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, regardless of the nature of the dust exposure, HRCT is known to be more specific and sensitive than CXR in identifying pneumoconiosis . Furthermore, HRCT is more sensitive than radiography in revealing small nodules in the subpleural area and fissures, emphysema, early fibrotic changes, subpleural lines and parenchymal bands in coal workers' pneumoconiosis and asbestosis .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a normal conventional roentgenogram in people exposed to dust does not exclude the presence of silicosis. CT can detect small and multifocal opacities more accurately and earlier than roentgenograms [10].…”
Section: Discussionmentioning
confidence: 98%
“…When FSR was ambiguous, HRCT was reported to be more sensitive than FSR in the detection of diffuse lung parenchyma diseases 10, 20−22) . Sun et al observed that 8 subjects were diagnosed as having early silicosis based on HRCT of 30 subjects whose diagnosis were non-silicosis on FSR according to the same criteria 23) .…”
Section: Discussionmentioning
confidence: 99%